Clinical Remission of Sight-Threatening Non-Infectious Uveitis Is Characterized by an Upregulation of Peripheral T-Regulatory Cell Polarized Towards T-bet and TIGIT - Gilbert, Rose M.; Zhang, Xiaozhe; Sampson, Robert D.; Ehrenstein, Michael R.; Nguyen, Dao X.; Chaudhry, Mahid; Mein, Charles; Mahmud, Nadiya; Galatowicz, Grazyna; Tomkins-Netzer, Oren; Calder, Virginia L.; Lightman, Sue (Frontiers in Immunology, 2018)
Background: Non-infectious uveitis can cause chronic relapsing and remitting ocular inflammation, which may require high dose systemic immunosuppression to prevent severe sight loss. It has been classically described as an autoimmune disease, mediated by pro-inflammatory Th1 and Th17 T-cell subsets. Studies suggest that CD4+CD25+FoxP3+ T-regulatory cells (Treg) are involved in resolution of inflammation and may be involved in the maintenance of clinical remission. Objective: To investigate whether there is a peripheral blood immunoregulatory phenotype associated with clinical remission of sight-threatening uveitis by comparing peripheral blood levels of Treg, Th1 and Th17, and associated DNA methylation and cytokine levels in patients with active uveitic disease, control subjects and patients (with previously active disease) in clinical remission induced by immunosuppressive drugs. Methods: Isolated PBMC from peripheral blood samples from prospectively recruited subjects were analysed by flow cytometry for CD3, CD4, FoxP3, TIGIT, T-bet and RORγ-t. Epigenetic DNA methylation levels of FOXP3 TSDR, FOXP3 Promoter, TBX21, RORC2 and TIGIT loci were determined in cryopreserved PBMC using an NGS sequencing approach. Related cytokines were measured in blood sera. Functional suppressive capacity of Treg was assessed using T-cell proliferation assays. Results: Fifty patients with uveitis (intermediate, posterior and panuveitis) and 10 control subjects were recruited. The frequency of CD4+CD25+FoxP3+ Treg, TIGIT+ Treg, T-bet+ Treg and the ratio of Treg to Th1 was significantly higher in remission patients compared to patients with active uveitic disease; and TIGIT+ Treg were a significant predictor of clinical remission.. Treg from patients in clinical remission demonstrated a high level of in vitro suppressive function compared to Treg from control subjects and patients with untreated active disease. PBMC from patients in remission had lower methylation levels at the FOXP3 TSDR, FOXP3 promoter and TIGIT loci and higher levels at RORC loci than those with active disease. Clinical remission was also associated with significantly higher serum levels of TGF-β and IL-10, which positively correlated with Treg levels, and lower serum levels of IFNγ, IL-17A and IL-22 compared to patients with active disease. Conclusion: Clinical remission of sight-threatening non-infectious uveitis has an immunoregulatory phenotype characterised by upregulation of TIGIT+ and Tbet+ Treg.